A modified reference area method to estimate creep behaviour of service-exposed Cr5Mo based on spherical indentation creep test. (November 2019) - Lu, Wenbin; Ling, Xiang; Yang, Sisheng
Abstract: In this study, indentation creep tests under different conditions were conducted using a self-designed vacuum high-temperature indentation creep device to investigate the creep properties of service-exposed Cr5Mo. A microstructure test was also conducted and a prominent pile-up was found on the surface of the specimen. We performed a comprehensive finite element analysis to evaluate the non-uniform deformation characteristics of the spherical indentation creep test. The stress distribution and stress evolution for indenters with different diameters were also estimated during the test. Subsequently, considering the difficulty of calculating the equivalent stress owing to the area variation during spherical indentation, a modified reference area method was proposed. Based on a load relaxation simulation and geometric factor analysis, a general formula for the reference areas of indenters with different diameters was given. Thus, the equivalent stress during spherical indentation could be calculated, and the creep behaviour of service-exposed Cr5Mo was estimated. The results when using the modified method in this study demonstrated good consistency with the results obtained by the standard method. To sum up, the spherical indentation creep test has prominent advantages over the uniaxial tensile creep test in the analysis of in-service components. Highlights: Creep behaviour of Cr5Mo was estimated using spherical indentation creep test. Non-uniform deformation characteristics of the test was analyzed by FEM. Stress distribution and stress evolution for distinct indenters were estimated. A modified reference area method for spherical indentation creep test was proposed. Equivalent stress during spherical indentation can be calculated using this method.